Exploring tennis coaches' insights in relation to their teaching styles - Pill, S.; Hewitt, M.; Edwards, K. (Baltic Journal of Sport and Health Sciences, 2016)
Background. The aim of this study was to explore junior tennis coaches` insights in relation to teaching styles they employ as well as the motivations and reasons that underpin these practices. Methods. The research consisted of implementing interviews with the 13 tennis coaches. It employed purposive or theoretical sampling. Semi-structured interviews commenced with a prearranged group of questions to permit scope in direction so that the interviewer may follow what is considered as pertinent to the interviewee. The coaches were filmed during three 30 minute sessions. Prior to the interviews, each of the coaches was requested to view a portion of their video-recorded sessions. The interview data were analysed via deductive content analysis. Results. The results highlighted a lack of knowledge concerning the theoretical and practical application of various teaching styles required for coaching tennis to junior players. The coaches lacked self-awareness with regard to their own coaching performance and were incapable of accurately describing the reasons why they implement particular ways of coaching. Coaches used an assortment of terms to identify the way they coach and that their decision to employ certain ways of coaching did not alter as a function of the age group, skill level or ability of the players they were coaching. Observing and/or discussing aspects of coaching with a mentor as well as playing experience had a greater influence on current coaching behaviour than attending an accreditation course. Conclusion. The finding from this study is that the personally anticipated coaching behaviour of the coach was not what they realised upon observation of their coaching.